Komunikasi Interpersonal Santri - Muhammad Munir; Lailatul Latifah (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2020)
Interpersonal Communication can occur in place, namely in boarding schools. If Interpersonal Communication doesn’t effectively do, there will be awkwardness in Communication. The phenomenon that occurs in santri in pesantren is closed Communication with seniors. Because it is awkward that makes interpersonal Communication of students becomes inappropriate because there is a sense that is embedded in students to senior students, as well as senior students of prestige to greet and give greetings to junior students. This research approach is a phenomenological study, while this type of research is qualitative. While interviews, observations and documentation are methods of collecting data. They consisted of Al-Amien Prenduan students and An-Nurriyah Surabaya students. Because this boarding schools has a strict discipline and found the difference. While data reduction, synthesis, compiling working hypotheses are as data analysis. Triangulation and extension of participation as checking the validity of the data. The results of this study are interpersonal Communication of junior and senior santri, the social behavior of junior and senior santri, social interaction of junior santri and senior santri, the doctrine of senior santri to junior santri, fanatic of junior santri and senior santri, bullying of junior santri and senior santri. Komunikasi interpersonal dapat terjadi di manapun termasuk pondok pesantren. Jika Komunikasi Interpersonal tidak dilakukan secara efektif maka akan terjadi kecanggungan dalam berkomunikasi, umumnya fenomena komunikasi yang terjadi antar santri di pesantren adalah komunikasi tertutup. Hal ini dikarenakan rasa canggung antara santri senior dan santri junior dalam berinteraksi, santri senior gengsi untuk menyapa dan memberikan sapaan kepada santri junior. Pendekatan penelitian ini adalah studi fenomenologi dengan menggunkan jenis penelitian kualitatif. Pengumpulan data menggunakan wawancara, observasi dan dokumentasi. Sedangkan reduksi data dan sintesisasi digunakan sebagai analisis data. Selain itu menggunakan triangulasi dan perpanjangan keikutsertaan untuk pengecekan keabsahan data. Hasil dari penelitian ini menggambarkan komunikasi interpersonal santri junior dan santri senior, perilaku sosial santri junior dan santri senior, intraksi sosial santri junior dan santri senior, doktrin santri senior kepada santri junior, fanatik santri junior dan santri senior, serta bullying santri junior dan santri senior.